2019
DOI: 10.1371/journal.pone.0226699
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Group B streptococcal virulence potential amongst vaginal clinical isolates from pregnant women

Abstract: Streptococcus agalactiae, also known as Group B Streptococcus (GBS), is a Gram-positive bacterium isolated from the vaginal tract of approximately 25% of women. GBS colonization of the female reproductive tract is of particular concern during pregnancy as the bacteria can invade gestational tissues or be transmitted to the newborn during passage through the birth canal. Infection of the neonate can result in life-threatening pneumonia, sepsis and meningitis. Thus, surveillance of GBS strains and corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…S1A to C in the supplemental material). Additionally, we determined how a panel of 27 vaginal isolates collected from the vaginal tracts of pregnant women ( 49 ) survived in the presence of calprotectin. All strains were grown with or without 120 μg/ml calprotectin, and data are displayed as percent inhibition in treated versus untreated controls for isolates belonging to five different capsular serotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1A to C in the supplemental material). Additionally, we determined how a panel of 27 vaginal isolates collected from the vaginal tracts of pregnant women ( 49 ) survived in the presence of calprotectin. All strains were grown with or without 120 μg/ml calprotectin, and data are displayed as percent inhibition in treated versus untreated controls for isolates belonging to five different capsular serotypes.…”
Section: Resultsmentioning
confidence: 99%
“… Streptococcus agalactiae (GBS) isolates A909 (serotype Ia), CJB111 (serotype V), COH1 (serotype III), a cohort of 25 vaginal colonization isolates (serotypes Ia, Ib, II, III, and V) ( 49 ), and mutant strains (A909 Δ adcA , A909 Δ adcAII , A909 Δ lmb , A909 Δ adcA Δ adcAII Δ lmb , and CJB111 Δ adcA Δ adcAII Δ lmb ) were cultured in Todd-Hewitt broth (THB) at 37°C. Mutant strains were constructed as previously described ( 40 , 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…The high resistance rates described by us prohibits empirical use of these antibiotics for women with penicillin allergy. The increasing reports regarding penicillin resistance [ 12 , 13 ] warrant also routine susceptibility test for penicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data reports increasing rates of macrolide resistance [ 10 , 11 ]. Also, several recent studies demonstrated a worrying increase in GBS isolates with resistance to penicillin [ 12 , 13 ]. In Israel, screening does not include antibiotic susceptibility and there is no data regarding GBS resistance rates.…”
Section: Introductionmentioning
confidence: 99%
“…The importance to identify GBS serotypes lies in their different abilities to cause disease. According to this potential, neonatal invasive disease and meningitis are prevalently due to virulent serotype III, whereas serotypes Ia, Ib, II, III, and V are recognized as the most common isolated strains associated with GBS disease [ 7 , 19 ]. Epidemiological studies, aimed to establish the predominant serotype/s in a specific country, could constitute a first step for the development of prevention strategies such as vaccines, which is being intensively worked on for several years [ 20 ].…”
Section: Introductionmentioning
confidence: 99%